OsSRO1a Interacts with RNA Binding Domain-Containing Protein (OsRBD1) and Functions in Abiotic Stress Tolerance in Yeast - Sharma, Shweta; Kaur, Charanpreet; Singla-Pareek, Sneh L.; Sopory, Sudhir K. (Frontiers in Plant Science, 2016)
SRO1 is an important regulator of stress and hormonal response in plants and functions by interacting with transcription factors and several other proteins involved in abiotic stress response. In the present study, we report OsRBD1, an RNA binding domain 1- containing protein as a novel interacting partner of OsSRO1a from rice. The interaction of OsSRO1a with OsRBD1 was shown in yeast as well as in planta. Domain–domain interaction study revealed that C-terminal RST domain of OsSRO1a interacts with the N-terminal RRM1 domain of OsRBD1 protein. Both the proteins were found to co-localize in nucleus. Transcript profiling under different stress conditions revealed co-regulation of OsSRO1a and OsRBD1 expression under some abiotic stress conditions. Further, co-transformation of both OsSRO1a and OsRBD1 in yeast conferred enhanced tolerance toward salinity, osmotic, and methylglyoxal treatments. Our study suggests that the interaction of OsSRO1a with OsRBD1 confers enhanced stress tolerance in yeast and may play an important role under abiotic stress responses in plants.